2014
DOI: 10.1016/j.foreco.2014.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host tree density and apparency on the probability of attack by the pine processionary moth

Abstract: a b s t r a c tThe pine processionary moth (PPM, Thaumetopoea pityocampa) is the main defoliator of pines in the Mediterranean area, necessitating constant surveillance and regular pest management. A sound understanding of the spatial distribution of infested trees, both within and between stands, is required to increase management efficiency. We hypothesized that both host tree density at stand scale and tree apparency at individual tree scale were responsible for between-and within-stand patterns of PPM infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 49 publications
7
30
1
3
Order By: Relevance
“…Here, we found that taller trees experienced higher herbivory and mildew, especially when growing in the context of less vigorous surrounding trees. For insect herbivores, apparency may determine host searching efficiency, as has been suggested previously for the pine processionary moth (Régolini et al, 2014). For powdery mildew, a passive, wind-dispersed pathogen (Marçais & Desprez-Loustau, 2014), spore interception may be more efficient when hosts are taller and therefore more prominent in the landscape.…”
Section: Positive Impacts Of Tree Vigor and Apparencymentioning
confidence: 75%
See 1 more Smart Citation
“…Here, we found that taller trees experienced higher herbivory and mildew, especially when growing in the context of less vigorous surrounding trees. For insect herbivores, apparency may determine host searching efficiency, as has been suggested previously for the pine processionary moth (Régolini et al, 2014). For powdery mildew, a passive, wind-dispersed pathogen (Marçais & Desprez-Loustau, 2014), spore interception may be more efficient when hosts are taller and therefore more prominent in the landscape.…”
Section: Positive Impacts Of Tree Vigor and Apparencymentioning
confidence: 75%
“…Direct effects of nonhost neighbor trees may cause associational resistance by influencing the microclimate of plots with knock‐on impacts on insects (Muiruri & Koricheva, ), or by interfering with olfactory cues used by pests to find hosts (Jactel, Birgersson, Andersson, & Schlyter, ). Tree species diversity may also modify plant apparency, which can be defined the height of focal trees relative to their surroundings, and has been shown to be an important predictor of insect herbivore loads on individual trees (Castagneyrol, Giffard, Péré, & Jactel, ; Régolini et al, ). Moreover, complex indirect effects of plant neighborhood identity on insect herbivory and pathogens may be mediated via modifications to plant traits, including foliar nutritional quality and defenses against herbivory (Castagneyrol et al, ; Forey et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…; Regolini et al . ). We demonstrated that herbivory differs among woody plant life forms, generally increasing with increases in average plant height (from dwarf shrubs to shrubs and then to trees).…”
Section: Discussionmentioning
confidence: 97%
“…However, Régolini et al (2014) found that there is no effect between tree density and the probability of attack of Thaumetopoea pityocampa on pure stands of Pinus pinaster between four and 61 years of age. These authors found that trees were more likely to be affected on edge plots than on inner plots, and the chance of attack increases with tree diameter; suggesting that taller trees were more likely to be attacked than smaller ones.…”
Section: Discussionmentioning
confidence: 91%
“…However, adult insects were detected at native forest fragments in ravines, using exotic plantations to feed and reproduce. According to Régolini et al (2014), it is probable that feeding resources (Eucalyptus camaldulensis trees) were abundant enough regarding Ectinogonia buquetti population, ensuring that females were able to find suitable habitats throughout the landscape. However, these assumptions could not be tested with data collected in this study, but may allow the design of future research in this area.…”
Section: Discussionmentioning
confidence: 99%